Morfometric evaluation of young buffalo males in two Argentinean herds - Gabriela Alejandra Koza; José Luis Konrad; Jesús Alfredo Berdugo; Norma Beatriz Mussart; Josefina Hernando (Revista Científica)
Bubaline production has increased substantially during the last few years, mainly in the northeastern provinces of Argentina. Exploring biometric parameters on bovine productive traits has driven the development of techniques for greater productivity and reproductive efficiency. This work aimed to evaluate live weight (LW), body score (BS), thoracic perimeter (TP), animal (cross, AH) sacrum height (SH), and scrotal circumference (SC) in 12-month-old buffalo males located in two farms in Corrientes Province (Itatí and Empedrado), Argentina. Linear regression and correlation between variables were evaluated. Forty males of the Mediterranean breed, 20 from each herd, were employed. Descriptive statistics and analysis of variance were performed, and the herd was considered a source of variation in a Randomized Block Design. The degree of linear association was verified by Pearson’s test, and linear regression analysis was applied to all the variables explored; Infostat software 2020 was used. The results obtained were LW 323,65±7,01 and 365,5±6,84 k, BS 3,28±0,1 and 3,63±0,1 cm, TP 163,65±1,62 and 169,13±2,56 cm, AH 117,7±0,90 and 125,15±1,37 cm, SH 123,58±1,35 and 126,98±2,13 cm, SC 19,28±0,44 and 21,15±0,69 cm for Empedrado and Itatí respectively. In the farm located in Itatí, the males showed higher LW, TP, HH, and SC values. A significant correlation between LW and TP and LW with AH, SH, and SC was observed in both herds. There were significant values of Pearson’s equation in the correlation between BS and SC in the animals from the Empedrado locality and when considering the animals from both locations, but not in those from the Itatí establishment. The correlation values between BS and SC were 0.37 for the locality of Empedrado, 0.28 for the animals from the locality of Itatí, and 0.33 when evaluating all animals together. It is concluded that exploring morphometric variables from an early age allows the follow-up of the growth and development of the buffalo males selected as future bulls, highlighting the significant correlation of scrotal circumference with the morphometric variables explored. Agroecological characteristics in the Itatí locality were more favorable, possibly translated into a greater body and isometric development of the testicles in the buffaloes of this area.